Bausteine translationsorientierter Sprachkompetenz und translatorischer Basiskompetenzen - Schmidhofer, Astrid; Wußler, Annette (innsbruck university press, 2020)
This volume presents papers of the conference "Components of Translation-oriented Language Competence and Basic Translation Competencies" which took place at the Department of Translation Studies of the University of Innsbruck on 22 and 23 September 2017. The programme of the conference comprised a variety of different topics of the field of translation teaching as, for example, the role of the students' mother tongue or A language in translator education, foreign language training for translators, and topics in general and specialised translation including instruments for teaching literary and legal translation. - Der vorliegende Band ist das Ergebnis der Tagung Bausteine translationsorientierter Sprachkompetenz und translatorischer Basiskompetenzen, die am 22. und 23. September 2017 am Institut für Translationswissenschaft der Universität Innsbruck stattfand. Im Rahmen der Tagung wurde ein breites Spektrum translationsdidaktischer Themen angesprochen, wie die Rolle der Mutter- bzw. Bildungssprache in der Übersetzerausbildung, die Fremdsprachenausbildung für Übersetzer sowie allgemeine und fachsprachliche translatorische Fragestellungen, darunter didaktische Instrumente in der Literatur- und Rechtsübersetzung.